Calcinosis in juvenile dermatomyositis: Updates on pathogenesis and treatment - Pinotti, Caitlan S.; Cannon, Laura; Dvergsten, Jeffrey A.; Wu, Eveline Y. (Frontiers in Medicine, 2023)
Calcinosis, or the deposition of insoluble calcium salts in the skin, subcutaneous tissue, fascia, tendons, and muscles, is a feared complication of juvenile dermatomyositis. Calcinosis is estimated to affect up to 40% of patients with juvenile dermatomyositis and contributes to significant disease morbidity. Calcinosis can be challenging to treat, and the most effective treatment remains unknown because of a lack of comparative studies. We aim to review the literature published in the last 5 years to summarize updates on the pathogenesis and treatment of calcinosis in juvenile dermatomyositis and describe future areas for research.